2010
DOI: 10.1177/0886260510368152
|View full text |Cite
|
Sign up to set email alerts
|

Association of Violence Against Partner and Former Victim Experiences: A Sample of Clients Voluntarily Attending Therapy

Abstract: The authors addressed the associations between childhood and adolescence victimization and partner violence in adulthood. Data were collected on 480 men voluntarily attending therapy with a semistructured interview that assessed (a) violent behavior, categorized as physical violence, physical controlling behavior, property violence, psychologically controlling behavior, psychological degradation, indirect aggression, or sexual violence and (b) victim experiences during childhood or adolescence, categorized as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…There are strong indications that these women are in need of therapeutic treatment. As mentioned previously, studies of male perpetrators of violence in intimate relationships have shown that six out of ten men undergoing therapy have experienced childhood violence themselves and have major problems with anxiety, depression and substance abuse (Rangul Askeland et al 2011). In a Norwegian interview study of mothers who inflicted violence on their children, Kruse and Bergman (2014) found that the mothers themselves had had earlier experiences of violence and had also subjected a partner or ex-partner to violence.…”
Section: Summary and Recommendations For An Improved Support Systemmentioning
confidence: 92%
“…There are strong indications that these women are in need of therapeutic treatment. As mentioned previously, studies of male perpetrators of violence in intimate relationships have shown that six out of ten men undergoing therapy have experienced childhood violence themselves and have major problems with anxiety, depression and substance abuse (Rangul Askeland et al 2011). In a Norwegian interview study of mothers who inflicted violence on their children, Kruse and Bergman (2014) found that the mothers themselves had had earlier experiences of violence and had also subjected a partner or ex-partner to violence.…”
Section: Summary and Recommendations For An Improved Support Systemmentioning
confidence: 92%
“…Although there are significant sociodemographic variations in women's IPV help seeking, recent research indicates that the strongest independent predictor of women's use of supports is fear of their lives being in danger (Barrett & St Pierre, 2011). There is some research on IPV perpetrators' help seeking (e.g., Askeland, Evang, & Heir, 2011;Hester, Ferrari, Jones, et al, 2015). Nonetheless, there appears to be a paucity of research on IPH perpetrators' help seeking (Dobash & Dobash, 2015;Eliason, 2009;Martin et al, 2007).…”
Section: Risk Factors For Iphmentioning
confidence: 99%
“…It appears that IPV perpetrators as a group have a high prevalence of relational trauma (Askeland, Evang & Heir, 2011; Dutton, 2007). Askeland (2015) found that the majority of men who sought help after having perpetrated IPV reported physical, emotional, or sexual abuse during their childhood.…”
Section: Relational Trauma Historymentioning
confidence: 99%